CIRA AND FISCAL COOPERATION: INSTITUTIONAL INNOVATION, REVENUE COLLECTION EFFICIENCY, AND THE PROTECTION OF PUBLIC ASSETS - Júlio Edstron Secundino Santos (Artefactum - revista de estudos interdisciplinares, 2026)
This study examined the Interinstitutional Asset Recovery Committees (Comitês Interinstitucionais de Recuperação de Ativos – CIRAs) as public governance mechanisms designed to strengthen the Public Revenue Administration and enhance the recovery of public claims arising from tax and asset-related offenses. The research was justified by the increasing complexity of economic crime, the growing sophistication of asset concealment schemes, and the need for institutional arrangements capable of integrating governmental competencies, improving administrative efficiency, and reinforcing fiscal justice. Within this framework, the study analyzed the historical evolution of the CIRAs, their constitutional, administrative, and tax law foundations, as well as their incorporation into the contemporary paradigm of collaborative governance, characterized by interagency coordination, strategic information sharing, and results-oriented management. Methodologically, the research adopted the hypothetical-deductive method, supported by a qualitative literature review, analysis of legislation, case law, and regulatory instruments, complemented by case studies of experiences developed in several Brazilian states. The investigation examined the organizational structure of the CIRAs, their institutional cooperation mechanisms, fiscal intelligence tools, and asset tracing and recovery strategies, identifying the factors responsible for improving the effectiveness of public asset recovery. The findings confirmed the initial hypothesis, demonstrating that coordinated action among tax administrations, Public Attorneys' Offices, Public Prosecutors' Offices, Judicial Police authorities, and other public institutions generated significant gains in efficiency, resource optimization, reduced administrative fragmentation, and strengthened the State's capacity to combat complex tax fraud. The study concluded that the CIRAs constitute a significant institutional innovation in Brazilian fiscal governance, capable of strengthening the protection of public assets, promoting greater tax compliance, safeguarding free competition, and enhancing the State's financial capacity to implement public policies. Accordingly, the institutionalization of CIRAs in all Brazilian states was identified as a strategic measure for improving governance, fiscal efficiency, and the effectiveness of public asset recovery.